Financing for the Post-pandemic Recovery : Developing Domestic Sovereign Debt Markets in Central America - Francois Clevy, Jean.; Pedras, Guilherme; Perez Ruiz, Esther (Washington, D.C. : International Monetary Fund, 2021)
The pandemic has urged countries around the globe to mobilize financing to support the recovery. This is even more relevant in Central America, where the policy response to cushion the pandemic's economic and social impact has accentuated pre-existing debt vulnerabilities. This paper documents the potential for local currency bond markets to diversify and expand financing for the recovery, lowering bond yields, funding volatility, and exposure to global shocks. The paper further identifies priority actions, both national and regional, to support market development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; Financial Markets and the Macroeconomy; Fiscal Policy; Sovereign Debt